Respuesta :

Answer:

(-1,13) (0,9) (3,-3)

Step-by-step explanation:

If x = -1, 0, 3 then you plug in all thos x's to get the y's

     y + 4(-1) = 9

      y + (-4) = 9

           + 4  + 4

        y = 13

                                   y + 4(0) = 9

                                        y = 9

                                                                    y + 4(3) = 9

                                                                     y + 12 = 9

                                                                         - 12 - 12

                                                                        y = -3

ACCESS MORE